STRATEGI PENGEMBANGAN PRODUK PADA USAHA SABLON WS FIVEHER SCREEN PRINTING DI TANA TORAJA - Gebi Buli; Mey E. Limbongan; Marchelin (ITB AAS Indonesia Surakarta, 2025)
This study aims to design a product development strategy for WS FIVEHER SCREEN PRINTING in Tana Toraja. The research uses a descriptive qualitative method with data collected through interviews with the business owner and customers. The data were analyzed using the SWOT method by identifying strengths, weaknesses, opportunities, and threats. The results show that WS FIVEHER SCREEN PRINTING is positioned in quadrant I of the SWOT Matrix, supporting an aggressive strategy. Recommended development strategies include community-based promotions, product diversification aligned with market trends, improving production efficiency, and optimizing social media to reach a wider market segment. Keywords: product development strategy; SWOT analysis; WS FIVEHER screen printing; print quality; local promotion; product diversification; production efficiency.